The study on intrinsic and extrinsic reward that effect employee’s motivation in Khalifa Production Sdn Bhd / Izatul Ashikin Roslan and Siti Sabirah Shahidan - Roslan, Izatul Ashikin; Shahidan, Siti Sabirah (Faculty of Business and Management, 2014)
Motivation is the management process influencing behavior of knowledge on what make people think. It contributes to the process of stimulating people to act and achieve specific goals. As motivation concern, reward system is an important tool for management use as the channel of employee’s motivation. Currently, the reward programs are implementing either in public or private sectors. Previous study indicates that there are many factors that influencing on level of employee’s motivation. Present research study was focused only on two factors which are intrinsic and extrinsic reward.